Integration Strategy of Green City Development With the Indragiri Rokan River Flow Area in the Capital Area of Solok Regency “Arosuka” - Gusmal Gusmal; Agus Irianto (Publikasi Indonesia, 2022)
This study formulates a green city development strategy in the capital city of Solok Regency in the